PENERAPAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DENGAN PERMAINAN KARTU READ OR PUNISHMENT PADA PENGUASAAN HURUF HIRAGANA - Wahyuni, Ade (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
Mastering Hiragana letters is very necessary in learning Japanese. The large number of letters makes it difficult for students to learn and sometimes students also feel bored to write them down in books. Therefore, an innovative learning model is needed in mastering Hiragana letters. The purpose of this study is to describe the application of Team Games Tournament (TGT) learning model with read or punishment card game on Hiragana mastery and to find out students' response to the application of Team Games Tournament (TGT) learning model with read or punishment card game on Hiragana mastery. This research uses qualitative research using a descriptive analysis approach. The source of data is class X SMA N 10 Padang students totaling 35 students. The instruments used were posttest questions, non-tests including observation sheets and student response questionnaires. The results of this study showed that most students responded positively as seen from the students' scores which had increased. This is evidenced by the results of the total percentage of the overall postest answer value and student questionnaires in the good and very good categories. Thus, it can be concluded that the application and student response to Thus, it can be concluded that the application and student response to the Team Games Tournament (TGT) learning model with read or punishment card games on the mastery of hiragana letters can be used as an alternative to learning the mastery of hiragana letters. Keywords: Cooperative team games tournament, read or punishment card game, Hiragana letters